2017
DOI: 10.1097/mpg.0000000000001424
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Sucrase‐isomaltase Deficiency

Abstract: The novel compound heterozygote V577G/C1531W SI mutations lead to lack of SI expression in the duodenal brush border, confirming the diagnosis of CSID. These cases of CSID extend the molecular spectrum of this condition, further directing a more adequate dietary intervention for the patient and newborn sibling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This study also confirmed presence of heterozygous SI gene mutations in symptomatic cases with varied disaccharidase deficiency patterns, including low sucrase with and without low isomaltase, and PDD (3,7,10,32,37). Moreover, 71% of abnormal cases had concurrent lactase deficiency.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study also confirmed presence of heterozygous SI gene mutations in symptomatic cases with varied disaccharidase deficiency patterns, including low sucrase with and without low isomaltase, and PDD (3,7,10,32,37). Moreover, 71% of abnormal cases had concurrent lactase deficiency.…”
Section: Discussionsupporting
confidence: 79%
“…In recent studies, compound and simple heterozygous CSID variants were detected in patients diagnosed with IBS (3,5). Other studies reported high prevalence of sucrase enzyme deficiency in duodenal biopsies from patients with functional gastrointestinal disorders (FGIDs), including functional dyspepsia (FD) and nausea (3,5,7,10,11).…”
Section: What Is Newmentioning
confidence: 99%
“…Patients with an onset of CSID in infancy typically present symptoms that include diarrhea and failure to thrive, as observed in our case. Patients with an onset of CSID in childhood or adulthood present milder symptoms with only chronic diarrhea and have normal growth rates (11). According to a summary of previously reported cases (2,(6)(7)(8)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), the incidence of CSID differs between females and males (19/60) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an onset of CSID in childhood or adulthood present milder symptoms with only chronic diarrhea and have normal growth rates (11). According to a summary of previously reported cases (2,(6)(7)(8)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), the incidence of CSID differs between females and males (19/60) (Table 1). However, in some of these cases, sex was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The SI gene, which encodes the SI enzyme, is located on chromosome 3 and harbors a number of rare pathogenic mutations across functional domains, including the sucrase domain, the isomaltase domain, the cytosolic tail, the transmembrane domain, the stalk region, and the trefoil 1 domain (Figure 2). [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] These variants are predicted to result in reduced SI function or complete loss of SI function, 26 and thereby CSID.…”
Section: Genetic Variation In the Sucrase-isomaltase Genementioning
confidence: 99%